Cambridge IGCSE Pphysics coursebook - Sang, David (Cambridge University Press Cambridge ; New York, 2010)
Cambridge IGCSE Physics matches the requirements of the revised Cambridge IGCSE Physics syllabus (0625). Cambridge IGCSE Physics has been developed to provide full support for the Cambridge International Examinations syllabus (0625). It is written in accessible language and features clear objectives and chapter summaries, exam-style questions and worked examples. It is highly illustrated in full colour throughout. The accompanying Student CD-ROM contains answers to questions in the book, multiple-choice questions and answers, and activity sheets including practical work. Now available in both print and e-book formats. The e-book includes both the print version and materials from the Student CD-ROM. A Workbook and Teacher's Resource CD-ROM are also available to accompany the course.